Whither Southeast Asia terrorism? - Acharya, Arabinda (Imperial College Press insurgency and terrorism series, 2015)
The aim of this book is to make a comprehensive assessment of the threats of terrorism and extremism in the region and of the policies and practices adopted by the regional countries to counter the same. It is also necessary to evaluate if the region has become a safer place after the decade-long fight.